Lymphoid follicles in antral mucosa: immune response to Campylobacter pylori?. Issue 12 (December 1989) - Stolte, M; Eidt, S
Abstract : The prevalence of lymphoid follicles in endoscopic biopsy specimens from normal antral mucosa (n = 220), mucosa with reflux gastritis (n = 104), and in cases with Campylobacter pylori-associated gastritis (n = 2544) was studied. In the latter group whether there were associations between degree and activity of gastritis and the prevalence of lymphoid follicles and between the occurrence of lymphoid follicles and the presence of intestinal metaplasia in the antrum were investigated. In cases with normal mucosa and in those with reflux gastritis lymphoid follicles were not detected, but mucosal lymphoid follicles were found in 1297 (54%) of the cases with C pylori-associated gastritis. The prevalence of lymphoid follicles in the antral mucosa depended on the degree and activity of the gastritis and also correlated with the presence of intestinal metaplasia. The development of lymphoid follicles in the mucosa of the antrum probably represents, primarily, an immune response to the colonisation of the mucosa by C pylori.